2019
DOI: 10.1039/c9cp03864g
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal silicide surface grafting by multiple functional groups and green optimization by mechanochemistry

Abstract: The functionalization by different coupling agents enabled to modify the properties of the surface of CrSi2 nanocrystallites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Its chemical composition, determined by EPMA, is highly homogeneous with a stoichiometry determined to be CrSi 1.96 with silicon vacancies. The refined lattice parameters a = 4.435(2) Å and c = 6.374 (6) Å are in good agreement with those determined in our previous study (a = 4.431 (7) A ̊and c = 6.365(5) A ̊). 4 All the peaks of the XRD patterns of the S1, S2, and S3 samples, shown in Figure 2a, are attributed to the CrSi 2 phase, evidencing their phase-pure character within the detection limits associated with this technique.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Its chemical composition, determined by EPMA, is highly homogeneous with a stoichiometry determined to be CrSi 1.96 with silicon vacancies. The refined lattice parameters a = 4.435(2) Å and c = 6.374 (6) Å are in good agreement with those determined in our previous study (a = 4.431 (7) A ̊and c = 6.365(5) A ̊). 4 All the peaks of the XRD patterns of the S1, S2, and S3 samples, shown in Figure 2a, are attributed to the CrSi 2 phase, evidencing their phase-pure character within the detection limits associated with this technique.…”
Section: Resultssupporting
confidence: 89%
“…However, their thermal conductivity remains about one order of magnitude larger than that of PbTe (about 10–15 W/m K at room temperature), which strongly limits their thermoelectric performance. Thus, CrSi 2 -based alloys (P6 2 22 space group) may become promising candidates for thermoelectric applications if their lattice thermal conductivity could be significantly lowered by alloying, nanostructuring, or a combination of both. In this regard, we recently investigated the effect of nanostructuring on the lattice thermal conductivity of CrSi 2 by mechanical ball milling and demonstrated that decreasing the grain size to 45 nm reduces λ l by a factor of ∼2 . Not only does this effect originate from an increase in the phonon scattering at the grain boundaries but also to an increase in the point-defect concentration that further scatters the propagating acoustic phonons.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the high diffusivity of Cr in the nanostructure and the active formation of a Cr-rich oxide layer [48,49]. According to the literature [50], the oxidation rate of CrSi 2 is determined by the diffusion of all the reaction components at lower temperatures (700-900 • C), whereas it is mainly controlled by the diffusion of chromium over cationic vacancies in the p-type Cr 2 O 3 lattice at higher temperatures. of CrSi2 is determined by the diffusion of all the reaction components at lower temperatures (700-900 °C), whereas it is mainly controlled by the diffusion of chromium over cationic vacancies in the p-type Cr2O3 lattice at higher temperatures.…”
Section: Siliconizing Stepmentioning
confidence: 99%